The detection of mutation within goat cell division cycle 25 A and its effect on kidding number. Issue 7 (12th December 2022) - Yang, Yuta; Sun, Xiaomei; Cui, Wenbo; Liu, Nuan; Wang, Ke; Qu, Lei; Pan, Chuanying
Abstract: Cell division cycle 25 A ( CDC25A ) accounts for an essential function on early folliculogenesis of female mammals, especially regulating the function of intra-ovarian, thus this gene is pinpointed as a candidate gene that influences the kidding number of goat. On this ground, the purpose of this study was to investigate whether the reported 20-nt nucleotide variants locus (rs639467625) of the CDC25A gene influences kidding number in Shaanbei white cashmere goat (SBWC). The χ 2 -test showed that there were more ID genotypes in mothers of multiple lambs than in mothers of single lambs. Interestingly, this indel locus was related to the first-born kidding number in the group of SBWC goats ( p < 0.05). Similarly, the result of the t -test was consistent with the result of the χ 2 -test, showed the kidding number of ID genotype individuals was large than that of II individuals ( p < 0.05). These findings proved that the different genotypes of CDC25A have impacts on goat kidding numbers. Thus, the results led us to speculate that the ID genotype of CDC25A was one of the main indel influencing goat kidding numbers. Simultaneously, this study was expected to provide useful DNA markers for superior individuals selection by marker-assisted selection (MAS) and make a contribution to goats breeding.